2020
DOI: 10.3390/su12020533
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Balance of Grasslands on the Qinghai-Tibet Plateau under Future Climate Change: A Review

Abstract: Climate change has brought significant impacts upon the natural ecological environment and human social development. The future carbon balance study has become an important part of research on the impacts of climate change. The Qinghai-Tibet Plateau (QTP) is a key area for studying climate change. Grassland, as a typical ecosystem of the QTP, embodies the sensitivity of the plateau to the climatic environment, so the carbon balance of grassland under future climate change conditions is important for studying g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 105 publications
0
4
0
Order By: Relevance
“…There are few land resources suitable for cultivated land, but it is more suitable for forage. The dominant ecosystem type in the QTP is the grassland ecosystem [20], which is essential for development of animal husbandry. Correspondingly, the residents in the QTP had higher consumption of beef, mutton, and milk, and lower consumption of vegetables and aquatic products than the residents in other regions.…”
Section: Introductionmentioning
confidence: 99%
“…There are few land resources suitable for cultivated land, but it is more suitable for forage. The dominant ecosystem type in the QTP is the grassland ecosystem [20], which is essential for development of animal husbandry. Correspondingly, the residents in the QTP had higher consumption of beef, mutton, and milk, and lower consumption of vegetables and aquatic products than the residents in other regions.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, research on the Tibetan Plateau and the impact of human activities has notably progressed 14 , 15 . Human activities and their ecological impacts on the plateau have been extensively investigated.…”
Section: Introductionmentioning
confidence: 99%
“…In the other hand, these authors showed that soil C stocks increase after land use changes from native forest to grassland (+8%), farmland to grassland (+19%), farmland to plantation (+18%), and farmland to secondary forest (+53%). The importance of grasslands is remarked by Leng et al (2020) [62] showing that the organic carbon content of a plateau meadow in China increased when the disturbance intensity was small. However, an apparent contradictory result from Deng et al (2016) [63] was observed with the landuse change from farmland to grassland, soil C sequestration change was not significant during 0-10 years, and then it was significantly increased.…”
Section: Land Management and Sommentioning
confidence: 95%